2009
DOI: 10.1097/fpc.0b013e3283307cba
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic association study of 30 genes with phenobarbital drug response in epileptic dogs

Abstract: Further replication and assessment of breed specificity is required before these markers can be considered as predictive of responsiveness to phenobarbital in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A recent genetic study screened 125 epileptic dogs representing 44 breeds for 384 SNP across 30 genes. 48 All of these genes were related to PB pharmacology. Five genes were suggested to have an association with PB response although they did not reach statistical significance (KCNQ3, SCN2A2, GABRA2, EPOX HYD, and ABC-B4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent genetic study screened 125 epileptic dogs representing 44 breeds for 384 SNP across 30 genes. 48 All of these genes were related to PB pharmacology. Five genes were suggested to have an association with PB response although they did not reach statistical significance (KCNQ3, SCN2A2, GABRA2, EPOX HYD, and ABC-B4).…”
Section: Discussionmentioning
confidence: 99%
“…In the ABCB1 gene, 18 SNP were found that were not further described but showed no statistically significant association with PB response. 48 The identification of the 4 bp deletion in the ABCB1 gene has been proven to be of clinical value to predict the response of an individual dog to a wide variety of xenobiotics and AEDs. Therefore, it would be valuable to identify polymorphisms in the ABCB1 gene that could be used as putative markers in order to make rational decisions concerning therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent epilepsy research in dogs mainly focuses on the identification of epilepsy genes, but interest in mechanisms of pharmacoresistance and the characterization of the clinical course are increasing . It is generally stated that pharmacoresistance can develop in up to 30% of dogs with epilepsy .…”
mentioning
confidence: 99%
“…Five ABC transporters were found to be up-regulated in the studies included in this analysis: ABCA6, ABCA8, ABCC4, ABCA2 and ABCB6. Of these five transporters, only ABCC4 has previously been studied in pharmacoresistant epilepsy (26,27). The identification in this study of hitherto-overlooked MDTs suggests that the search for drug transporters relevant to epilepsy pharmacoresistance needs to be expanded beyond the selected few candidates which have been studied so far.…”
Section: Mdt Hypothesismentioning
confidence: 95%